Prokrastinasi Akademik: Studi Komparasi Siswa Ditinjau dari Jenis Kelamin dan Jenis Sekolah - Novirson, Rizki; Putri, Yola Eka (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
Academic procrastination is one of the many phenomena experienced by students. It has become a serious issue at the senior high school level. The purpose of this study is to describe the differences in students' academic procrastination levels based on gender and school type, namely regular schools and boarding schools. This study used a quantitative method with a comparative descriptive approach. 150 students in senior high school and vocational school became the research sample. Data were collected by Academic Procrastination Scale. Data analyzed used ANAVA. The results showed that (1) there is a significant difference in students' academic procrastination in terms of gender, (2) there is a significant difference in students' academic procrastination in terms of regular school and boarding school, (3) there is no interaction of academic procrastination in terms of gender and school type. This means that the interaction between gender and school type does not determine students' academic procrastination. Teachers and counselor have a big responsibility to help students get out of the problem of academic procrastination with counseling services.